An Analysis of the Smart Indonesia Card-College (KIP-Kuliah) Program in Supporting Poverty Alleviation - Vike Agestian Frastami; Kirani Felita June; Indah Prabawati; Firre An Suprapto (LP3M KH Yazid Karimullah Institute, 2026)
The Indonesia Smart Card for College (KIP-K) program is a government policy aimed at expanding access to higher education for underprivileged communities while simultaneously supporting poverty alleviation efforts, in line with the Sustainable Development Goals (SDGs) point 1, namely No Poverty. This study aims to analyze the implementation of the KIP-K program using William N. Dunn's policy evaluation indicators, which include effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The study uses a qualitative approach through a literature study method by reviewing scientific journals, government reports, policy documents, and various other relevant sources. The results show that the KIP-K program has made a positive contribution to increasing access to higher education and reducing economic barriers for students from underprivileged families. However, the implementation of the program still faces several obstacles, such as inaccurate targeting of aid recipients, delays in disbursement of funds, adequacy issues in certain regions, weak supervision, and less than optimal transparency in program management. These findings indicate that the success of the program is not only determined by the amount of educational assistance provided, but is also influenced by the quality of governance, recipient data validation, and the policy evaluation system implemented. Therefore, strengthening the evaluation mechanism and program governance is an important step in increasing the effectiveness of KIP-K to support sustainable poverty alleviation.